UGT concentrations in human rectal tissue after multidose, oral curcumin. Issue 2 (23rd February 2016) - Asher, Gary N.; Fallon, John K.; Smith, Philip C.
Abstract: In vitro studies have demonstrated that curcumin is a substrate for uridine diphosphate glucuronosyltransferase (UGTs), with a putative ability to both induce expression and inhibit function, highlighting the potential for interaction with some drugs. Therefore, we sought to evaluate the effect of oral curcumin on intestinal UGT expression. Healthy volunteers, ages 40–80 years, who had received recent screening colonoscopy were recruited. Participants did not have any gastrointestinal or bleeding disorders, lab abnormalities, or recent antibiotic use. All participants received daily curcuminoid extract, 4 g, for 30 days. Untreated, rectal mucosal pinch biopsies were obtained at baseline and at 30 days. Microsomes were prepared from biopsy samples, using sequential centrifugation. Quantification of 14 UGT 2As and 2Bs was performed by LC‐MS/MS(MS, mass spectrometry), using quantitative‐ targeted absolute proteomics. Lowest LODs were ~0.1 pmol/mg protein. Comparisons were performed using Wilcoxon signed‐rank test. Paired baseline and 30 days biopsy samples were available for 38 participants. UGTs 1A10 and 2B17 were detected in 35 and 33 paired samples, respectively, while all other UGTs were below the limit of quantification (BLOQ). Median baseline UGT1A10 concentration was 0.60 pmol/mg (95% CI:0.32–0.92), and 0.60 pmol/mg (95% CI:0.43–1.00) after 30 days ( P  = 0.23). For UGT2B17, median baseline concentration was 0.83 pmol/mg (95% CI:0.32–1.62), and 1.18 pmol/mg (95% CI:0.39–1.77) after 30 days ( P  = 0.24). We found no differences in rectal mucosal UGT concentrations before and after 30 days of oral curcumin administration, indicating that daily curcumin use is unlikely to alter colonic UGT expression. Distal gut biopsies may not accurately reflect the proximal gut environment where UGT expression and curcumin concentrations may be higher.